Management of spontaneous carotid artery rupture: navigating life-threatening challenges and persistent risks - Andreia Pinelo; Daniel Mendes; Joana Martins; Samuel Cardoso; Rui Machado (Angiologia e Cirurgia Vascular)
BACKGROUND: Carotid pseudoaneurysms are extremely rare, and their inherent instability and unpredictability require prompt evaluation and intervention to mitigate potential neurological complications or prevent life-threatening bleeding and airway obstruction. We present a case report of spontaneous internal carotid artery (ICA) rupture.